EVALUATION FOR USER’S SATISFACTION ON PATHWAY AND STREET FURNITURE FACILITIES IN THAMRIN-SUDIRMAN AREA - Yaseri Dahlia Apritasari (Department of Architecture Universitas Muhammadiyah Jakarta, 2020)
The Global Climate Change Problem is a global problem throughout the world. This requires the attention of all countries to commit to reducing carbon foot print by reducing the use of private vehicles. One way of their lives. So the development of cities when they need to be designed using carbon fooprint. Design cities to encourage people to use public transportation and motivate people to walk. The Thamrin and Sudirman Areas are trade and service centers, and primary activity centers, as well as a strategic area (Integrated Commerce Center and Upper Hamlet area are exchanges of mass public transport (TOD)) (Spatial Planning for DKI Jakarta Province in 2010-2030 ). As a provincial strategic area, for the past 5 years the DKI Provincial government has built pedestrian and public transportation facilities to improve the convenience of pedestrian and public transportation users. This study discusses road user satisfaction with pedestrian facility requirements: lanes, road furniture, and nameplates in the Thamrin Sudirman area. This study discusses user satisfaction in pedestrian facilities in the Thamrin Sudirman area. Locations in Thamrin Sudirman: Sarinah, Bunderan Hotel Indonesia, Dukuh Atas, Setia Budi-Chase Plaza, Hilir-Atmajaya Dam, Bung Karno Gelora, Sudirman-MRT Senayan-Ratu Plaza, and ASEAN MRT area. Survey assessment tools based on satisfaction levels of 1-9 scale, with criteria for elements: (1) path (Property, design, quality, hallway, shade, lighting, user friendliness, landscaping, maintenance, environment), (2) Street furniture and signage (Furniture and road shades, lamp post placement, information boards, signage). The results showed the Sudirman-MRT Senayan-Ratu Plaza area and the Gelora Bung Karno area, as a road that was considered to have a high level of satisfaction for pedestrians. Pathway design, street furniture and signage can fulfill pedestrian satisfaction. Thus it is expected that the design of pedestrian paths in these locations can be a reference for the design of pedestrian facilities. Keywords: satisfaction, users, pathways, street furniture